Diseño del manual de funciones del área de producción de la empresa Truchera el Oasis S.A.S (2018)
The company Truchera El Oasis, is a company dedicated to aquaculture, in the line of fish farming. Specialists in the cultivation of rainbow trout. Recognized at regional and departmental level for the quality of its product. Its main processes are the raising, raising and fattening of salmon trout, cultivated in tanks made of cement, freshwater; They make the sacrifice of the fish to meet the ideal weight to be sold to different customers, mainly restaurants.